Effects of Race and Socioeconomic Factors on Emergency Department Management of Threatened Abortion [26J]. Issue 1 (May 2017) - Cheng, Connie; Bernstein, Steven; Fan, Linda; Evans, Leigh
Abstract : INTRODUCTION: Among women presenting with pregnancy-related complications, demographically-based differences in incidence, outcomes, and treatment are known. Here we determine the effects of race, insurance, and hospital characteristics on threatened abortion management. METHODS: Patient record files from National Hospital Ambulatory Medical Care Survey with diagnosis of threatened abortion, hemorrhage in pregnancy, or incomplete or unspecified spontaneous abortion from 2002-2010 were examined using logistic regression. Primary outcomes were rates of admission and active management (surgical or pharmacological treatment). Covariates included race/ethnicity, age, insurance, and hospital location, ownership, and metropolitan status. RESULTS: Of 5, 882, 623 ED visits for threatened abortion, 15% were admitted; 1.3% were actively managed. Compared to white women, black women were less likely to be admitted (0.83, 95% CI 0.83-0.84), but more likely be actively managed (OR 4.37, 95% CI 4.25-4.50). Admission was more likely for "Other" women of color (OR 2.14, 95% CI 2.11-2.17), Medicaid/SCHIP (OR 1.24, 95% CI 1.22-1.25) and Self-paying women (OR 1.04, 95% CI 1.03-1.05). Historically-marginalized groups, including uninsured, black, and "Other" women, were more likely to be actively managed. Exceptions were Latina (OR 0.84, 95% CI 0.80-0.89) and Medicaid/SCHIP-insured women (OR 0.13, 95% CI 0.12-0.15). CONCLUSION: Black women are less likely than white women to be admitted for threatened abortion, but more likely to be actively managed. Other nonwhite and uninsured women are more likely to be admitted and actively managed, excepting Latinas. The etiology of these disparities is complex. Providers may seek to better understand their own preconceptions of patient risk, and to improve social support and shared decision-making.